The Persuasiveness of a Humorous Environmental Narrative Combined With an Explicit Persuasive Appeal. Issue 4 (August 2019) - Moyer-Gusé, Emily; Tchernev, John M.; Walther-Martin, Whitney
Entertainment narratives commonly feature explicit appeals to underscore important content therein. This strategy may also undermine the subtle approach that characterizes narrative persuasion. This experiment examined the effects of a pro-environmental public service announcement (PSA) combined with an entertainment narrative on environmental intentions and behaviors. Results revealed that the combination of an environmental narrative and PSA led to fewer intentions to engage in environmentally friendly behaviors than exposure to the environmental narrative alone. The PSA combined with the environmental narrative also led to greater perceived persuasive intent and, among those who held negative views about the environment, greater reactance and less environmentally friendly behavior.